THE APPLICATION OF MARKOWITZ METHOD IN ESTABLISHING STOCK AND OPTION PORTFOLIO - Evelyn, Sheren
The rapid development of technology and information has brought the Indonesian capital market to become a popular alternative investment method among the society, one of the popular investment instruments is mutual fund. This study aims to compare the performance of mutual fund reconstruction using Markowitz portfolio optimization method and the performance of call option during the pandemic and non-pandemic periods, compare the performance of mutual fund reconstruction with the actual performance of the studied mutual funds, and observe the effect of the portfolio formation frequency. The optimal portfolio construction method used is Markowitz method. The main objective of this method is to maximize the return and minimize the investment risk. The construction of optimal stock portfolio in this study depends entirely on the historical return data for each stock. Using 10 stocks/assets with the highest composition in Schroder Dana Istimewa mutual fund, optimal portfolio simulation is carried out on non-pandemic (year 2018) and pandemic (year 2021) condition. Based on the simulation results, it can be concluded that the impact of the pandemic is not very visible in the formation of an optimal portfolio using the classical method and also in the case of purchasing call options. The returns obtained during non-pandemic condition are relatively lower than during the pandemic condition, and returns from call options purchase are not significantly different. The performance of Markowitz portfolio optimization method is better than the mutual fund actual performance, and the frequency of portfolio construction is considered not to have much effect on the return obtained.